The protective role of oily fish intake against type 2 diabetes: insights from a genetic correlation and Mendelian randomization study - Zhang, Youqian; Ren, Entong; Zhang, Chunlong; Wang, Yang; Chen, Xiaohe; Li, Lin (Frontiers in Nutrition, 2024)
Background and aims Previous research has underscored the association between oily fish intake and type 2 diabetes (T2DM), yet the causality remains elusive. Methods A bidirectional univariable Mendelian Randomization (MR) analysis was employed to evaluate the causal effects of oily fish and non-oily fish intake on T2DM. Replication analysis and meta-analysis were conducted to ensure robust results. Multivariable MR analysis was utilized to assess confounders, and further mediation MR analysis discerned mediating effects. Linkage Disequilibrium Score (LDSC) analysis was undertaken to compute genetic correlations. Inverse variance weighted (IVW) was the primary method, complemented by a series of sensitivity analyses. Results The LDSC analysis unveiled a significant genetic correlation between oily fish intake and T2DM (Genetic correlation: -0.102, p = 4.43 × 10−4). For each standard deviation (SD) increase in genetically predicted oily fish intake, the risk of T2DM was reduced by 38.6% (OR = 0.614, 95% CI 0.504 0.748, p = 1.24 × 10−6, False Discovery Rate (FDR) = 3.72 × 10−6). The meta-analysis across three data sources highlighted a persistent causal association (OR = 0.728, 95% CI 0.593 0.895, p = 0.003). No other causal effects were identified (all p > 0.5, FDR > 0.5). The main outcomes remained consistent in most sensitivity analyses. Both MVMR and mediation MR analyses emphasized the mediating roles of triglycerides (TG), body mass index (BMI), and 25-hydroxyvitamin D (25OHD) levels. Conclusion To encapsulate, there’s an inverse association between oily fish intake and T2DM risk, suggesting potential benefits of oily fish intake in T2DM prevention.